Capital accumulation and technology transfer : - Thomas, D. Babatunde (Praeger, 1975)
This book introduce about background the Nigerian economiy and the role of capital accumulation in the manufacturing industries. Foreign technology and the development of indigenous technology. Capital, accumulation, thechnology transfer, and economic development...